Membangun Konsep Diri Dalam Buku Lembaga Budi Karya Haji Abdul Malik Karim Amrullah - Fitroh Qudsiyyah; Banatus Solihah (QALAM: JURNAL PENDIDIKAN ISLAM, 2021)
This research is motivated because the current condition of humans find it difficult to recognize who they are so they are easily influenced by outsiders who can plunge into things that lack truth values. There are two factors that influence human development, namely from nature and the environment. Because in addition to internal factors, there will be external factors that follow. Innate is an internal factor. A good trait is largely influenced by the quality of a good generation. Likewise with the environment as an external factor. It is undeniable that most of human life is spent in the environment. Both the family environment and the community environment. These factors can affect the mindset of humans in recognizing themselves and the environment. In recognizing yourself, self-concept is very important so that you can recognize your potential and everything you will do can be considered carefully. But knowing yourself is not enough in self-management. Just as planning is meaningless without implementation. Self-concept also needs to be built so that the action goes well. The author chose Hamka because he is an Indonesian cleric, writer and Sufism figure. So a lot of knowledge can be obtained from his works.